The big trees [videorecording (DVD)] - Feist, Felix E., 1906-1965; Douglas, Kirk, 1916-2020-; Miller, Eve, 1923-1973; Wymore, Patrice, 1926-2014 (Digiview Proeuctions, 2004)
Douglas is at his brash and charming best as a rowdy, brawling lumberjack who abandons his roguish ways and some rather unscrupulous business practices when he falls in love with a beautiful young Quaker woman.